Cutaneous fistulization of the hydatid disease: A PRISMA-compliant systematic review - Bahce, Zeynep Sener (Medicine (Baltimore), 2016)
AIM: To provide an overview of the medical literature on cutaneous fistulization in patients with hydatid disease (HD). METHODS: According to PRISMA guidelines a literature search was made in PubMed, Medline, Google Scholar, and Google databases were searched using keywords to identify articles related to cutaneous fistulization of the HD. Keywords used were hydatid disease, hydatid cyst, cutaneous fistulization, cysto-cutaneous fistulization, external rupture, and external fistulization. The literature search included case reports, review articles, original articles, and meeting presentations published until July 2016 without restrictions on language, journal, or country. Articles and abstracts containing adequate information, such as age, sex, cyst size, cyst location, clinical presentation, fistula opening location, and management, were included in the study, whereas articles with insufficient clinical and demographic data were excluded. We also present a new case of cysto-cutaneous fistulization of a liver hydatid cyst. RESULTS: The literature review included 38 articles (32 full text, 2 abstracts, and 4 unavailable) on cutaneous fistulization in patients with HD. Among the 38 articles included in the study, 22 were written in English, 13 in French, 1 in German, 1 in Italian, and 1 in Spanish. Forty patients (21 males and 19 females; mean age ± standard deviation, 54.0 ± 21.5 years; range, 7–93 years) were involved in the study. Twenty-four patients had cysto-cutaneous fistulization (Echinococcus granulosus); 10 had cutaneous fistulization (E multilocularis), 3 had cysto-cutaneo-bronchio-biliary fistulization, 2 had cysto-cutaneo-bronchial fistulization; and 1 had cutaneo-bronchial fistulization (E multilocularis). Twenty-nine patients were diagnosed with E granulosis and 11 had E multilocularis detected by clinical, radiological, and/or histopathological examinations. CONCLUSION: Cutaneous fistulization is a rare complication of HD. Complicated HD should be considered in the differential diagnosis of cases presenting with cutaneous fistulization, particularly in regions where HD is endemic.